Impact of heat treatment on spark plasma sintered magnesium-containing lightweight AlFeCuCrMg high entropy alloy - Dewangan, Sheetal Kumar; Maulik, Ornov; Kumar, Devesh; Kumar, Saurav; Kumar, Vinod; Ahn, Byungmin (Journal of Materials Research and Technology, 2023)
In this study, the impact of heat treatments on AlFeCuCrMgx (x = 0, 0.5, 1, and 1.7) alloys prepared by mechanical alloying and spark plasma sintering were examined. The behavior of these high-entropy alloys (HEAs) was thoroughly studied after they had been heated to 470, 600, and 820 °C in a natural atmosphere. X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) were used to study the phase evolution of the heat-treated alloys. The XRD data of the AlFeCuCrMgx (x = 0 and 0.5) alloys heated at 470, 600, and 820 °C present the dispersion of FCC Cu particles at the grain boundaries of parental phases. By contrast, the AlFeCuCrMgx (x = 1 and 1.7) alloys do not exhibit this characteristic. The microstructures of these alloys have been correlated with these results. Their sub-micron structures indicate that the precipitates are unaffected up to 820 °C. The impact of elevated temperatures on the AlFeCuCrMgx alloys was thoroughly examined based on conventional theory.
Keywords: Electron transmission; Grain-boundaries; Heat treated alloy; High entropy alloys; Phase evolutions; Phases transformation; Spark plasma; Spark-plasma-sintering; X- ray diffractions; X-ray diffraction data; Diffusion; Heat treatment; High entropy alloy; Phase transformation; Powder metallurgy